Delayed Effect of Superheated Steam Treatment on Starch Retrogradation of Rice Cake After Storage by Modifying Starch Chain-Length Distribution in Rice Flour - Ruge Cao; Zixiu Zhang; Xishuang Wang; Chen Xia; Yongqiang Cheng; Zhiwei Wang; Ju Qiu (Molecules)
This study investigated the effects of superheated steam (SS) treatment on the physicochemical properties of rice flour and the subsequent impact on rice cake quality. The SS-180 resulted in higher final viscosity and significantly increased pasting time and the temperature of rice flour (p < 0.05). A significant enhancement in the water holding capacity of rice flour (p < 0.05) was due to the rice starch aggregated in this SS process. SS treatment also led to an increase in the proportion of short chains of amylopectin in rice flour from 30.40% to 37.59%, while a decrease in long chains retarded retrogradation and improved rice cake texture. The hardness of the SS-treated rice cake was lower than that of the untreated one, but the specific volume was increased significantly (p < 0.05). After 7 days of storage, rice cake with SS-180 treatment showed the lowest hardness, namely, the lowest retrograded process. These findings underscore the potential of SS treatment to enhance the physicochemical properties of rice flour and improve rice cake quality.